Operations Strategy and Airport Development - Boehm, Roland (2006)
Executive Summary The airport business is taking off. During the last twenty-five years the airport in-dustry has been transformed from being a branch of government into a dynamic and commercial orientated business (Doganis, 1992). The worldÃÂÃÂÃÂÃÂ¢ÃÂÃ¢ÂÂÃÂÃ¢ÂÂ¬ÃÂÃ¢ÂÂÃÂÃ¢ÂÂ¢s airports served over 4 billion passengers in 2005, a new record for the industry. Passenger traffic was up 6% over 2004, with strong growth in all regions. (ACI 2006a). In order to cope with that additional demand, airport operators are faced with the challenging task to provide additional capacity for the next decade. Since these capital investments representing a major part of the overall investments and influences the airport fixed cost base significantly, it is important to have a clear strategy behind the expansion projects. In the field of Operations Management a similar significance was early recognised and proved by Skinner (1969) in manufacturing in-dustries. He suggested the principals of an Operations Strategy. Later Hayes and Wheelwright (2005) introduced four basic structural decisions in operations every man-ager has to make. These are related to capacity, facilities, vertical integration and infor-mation technology. In this study, three frameworks were developed to link the economical performance of an airport to a consistent set of strategic capacity and facility decisions. By applying these frameworks in a case study setting to five (FRA, PHL, SIN, VIE, YVR) international airports, it was shown that the principals of Operations Strategy are not totally applied throughout the sample. Some attempts are made to link strategy with operations and airport development but the extend varies among the different cases. In addition, the available data for performance model was not sufficient to isolate specific structural decisions and judge on the change in performance. Nevertheless, some very good examples for a systematically link between opera-tions and strategy could be found. At YVR, a structured planning process starts build on a 20+ years strategic plan and subsequently breaks this plan down to the annual busi-ness plan.